STATUS KEBERLANJUTAN PENGELOLAAN EKOSISTEM MANGROVE DI WILAYAH PESISIR DESA AKUNI KECAMATAN TINANGGEA KABUPATEN KONAWE SELATAN Sustainability Management Status of Mangrove Ecosystem in Coastal Area of Akuni Village District of Tinanggea, South Konawe - Muhsimin .; Nyoto Nyoto Santoso; Hariyadi . (Jurnal Silvikultur Tropika, 2018)
This study aims to analyze the sustainability status of mangrove ecosystem management in coastal areas of Akuni Village by integrating all interests in multidimensional (ecological, economic, social, and institutional) and determining sensitive indicators in sustainability management of mangrove ecosystem. The method used in this study was Rapid Appraisal for Fisheries (RAPFISH) based on multidimensional scaling (MDS). The results showed that the multidimensional sustainability status of mangrove ecosystem management in coastal area of Akuni Village was less sustainable (46.67%); Ecological dimension of 73.29% (sustainable enough); Economic dimension of 53.77%(sustainable enough); Social dimension of 38.32% (less sustainable); Institutional dimension of 25.36% (less sustainable). Improvement efforts toward sensitive indicators on each dimension are necessary to minimizeenvironmental quality degradation especially for mangrove ecosystem due to anthropogenic activity. Those dimension indicators improvement expected to give some positive feedback for managers in order to improve the sustainabilitystatus of mangrove ecosystem management in a multidimensional manner.Key words: Akuni Village, Multidimensional scaling (MDS) mangrove ecosystems, Sustainability index and status